Pride and Prejudice on the Page and on the Screen: Literary Narrative, Literary Dialogue and Film Dialogue - Bianchi, Francesca; Gesuato, Sara (Nordic Journal of English Studies, 2020)
This study explores the similarities and differences in content between the dialogic and the narrative parts in Jane Austen’s Pride and Prejudice, and between the novel’s dialogues and those in its 1940 and 2005 film adaptations. These four datasets were semantically tagged and compared to one another by using qualitative and quantitative methods. The findings show how, in covering conceptual areas largely complementary to those of the narrative, the dialogues in the novel perform various communicative functions. The investigation also points to how dialogues are adapted to the semiotic needs and goals of its film adaptations.